The Role of FRMD7 in Idiopathic Infantile Nystagmus - Rachel J. Watkins; Mervyn G. Thomas; Chris J. Talbot; Irene Gottlob; Sue Shackleton (Journal of Ophthalmology)
Idiopathic infantile nystagmus (IIN) is an inherited disorder in which the nystagmus arises independently of any other symptoms, leading to the speculation that the disorder represents a primary defect in the area of the brain responsible for ocular motor control. The inheritance patterns are heterogeneous, however the most common form is X-linked. FRMD7 resides at Xq26-27 and approximately 50% of X-linked IIN families map to this region. Currently 45 mutations within FRMD7 have been associated with IIN, confirming the importance of FRMD7 in the pathogenesis of the disease. Although mutations in FRMD7 are known to cause IIN, very little is known about the function of the protein. FRMD7 contains a conserved N-terminal FERM domain suggesting that it may provide a link between the plasma membrane and actin cytoskeleton. Limited studies together with the knowledge of the function of other FERM domain containing proteins, suggest that FRMD7 may play a role in membrane extension during neuronal development through remodeling of the actin cytoskeleton.